A prospective observational study of role of epidural in trial of labour after cesarean section in view of maternal and neonatal outcome in a tertiary care hospital - Sundaram, Jothi; Vinoth, Divya; Sriram, Malathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In a well-equipped hospital, trial of vaginal delivery is done in selected cases of previous C-section (CS). Epidural analgesia administration has been proved to be good adjunct in trial of labor after caesarean (TOLAC). Methods: This study is a prospective observational study done in a tertiary care institution in Tamil Nadu from May 2019 to July 2019. 50 cases with previous history of one CS were selected. Single ton pregnancy, previous transverse lower segment cesarean section admitted cases with adequate pelvis with no other co-morbidities were selected. Epidural analgesia was administered once mother was in established labor. TOLAC was continued till satisfactory progress and emergency repeat caesarean was taken in case of Suspected scar dehiscence (SSD) or abnormal fetal heart rate tracings. Quantitative data was expressed in mean and standard deviation. For qualitative data percentage was used. Results: In 50 cases observed the mean age of the cases was 26±3.64 years. TOLAC was successful in 41 (82%) mothers out of 50. The mode of delivery in 41 TOLAC mothers was found to be forceps in 18 cases (36%) and ventouse delivery 18 cases (36%). Only 9 cases had needed emergency CS (18%). The major indication for CS in TOLAC was found to be fetal distress in 4 number of cases (8%). 43 babies delivered were healthy, 6 babies (12%) admitted in NICU. Conclusions: With the application of epidural analgesia on attempted vaginal delivery in previous cesarean, vaginal delivery was 82% cases.